2020
DOI: 10.1111/jgs.16918
|View full text |Cite
|
Sign up to set email alerts
|

Impact of an Advance Care Planning Video Intervention on Care of Short‐Stay Nursing Home Patients

Abstract: BACKGROUND/OBJECTIVES To assess whether an advance care planning (ACP) video intervention impacts care among short‐stay nursing home (NH) patients. DESIGN PRagmatic trial of Video Education in Nursing Homes (PROVEN) was a pragmatic cluster randomized clinical trial. SETTING A total of 360 NHs (N = 119 intervention, N = 241 control) owned by two healthcare systems. PARTICIPANTS A total of 2,538 and 5,290 short‐stay patients with advanced dementia or cardiopulmonary disease (advanced illness) in the intervention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 43 publications
1
19
0
Order By: Relevance
“…This outcome was assessed by 22 RCTs 24 25 33–35 37 41 42 54 57 66 68 69 109–117. Of these four (18%) RCTs68 109–111 showed significantly reduced healthcare use/costs.…”
Section: Resultsmentioning
confidence: 99%
“…This outcome was assessed by 22 RCTs 24 25 33–35 37 41 42 54 57 66 68 69 109–117. Of these four (18%) RCTs68 109–111 showed significantly reduced healthcare use/costs.…”
Section: Resultsmentioning
confidence: 99%
“…Third, improved advanced care planning around the hospital to postacute care transition is needed to avoid postacute care stays that are more consistent with harm than benefit 13 . Risk prediction scores have been developed to identify patients at high risk for adverse outcomes in SNF and HH, and several advanced care planning interventions in SNF are being tested in trials 30–34 . However, these efforts may be occurring too late in the care trajectory (e.g., once the patient is already in SNF).…”
Section: Discussionmentioning
confidence: 99%
“…Mitchell et al 26 and Loomer et al 23 found no effect on hospital transfers per 1000 person-days alive for nursing home residents with long stay (>100 days) and short stay (<100 days). Two RCTs 23,26 reported on transfers and hospitalizations. Midquality evidence (rated down for imprecision) suggests no significant reduction in hospital transfers (RR, 1.00; 95% CI, 0.99-1.02; I 2 = 48%; heterogeneity P = .17; Supplemental Appendix 2, Figure 9, http://links.lww.com/JHPN/A91; P = .71).…”
Section: Hospital Transfermentioning
confidence: 96%
“…Three RCTs 19,24,27 were ranked as high-quality studies. Allocation concealment was high risk in 7 14,17,18,[20][21][22][23] RCTs and unclear in 1 RCT. 25 Blinding of participants and personnel was high risk in 2 RCTs 15,23 and unclear in 1 RCT, 16 and blinding of outcome assessment was high risk in 5 RCTs 14,18,[20][21][22] and unclear in 2 RCTs.…”
Section: Study Quality Assessment and Risk Of Biasmentioning
confidence: 99%